APPLICATION OF INFORMATION COMMUNICATION TECHNOLOGIES IN THE STUDY PROCESSES OF THE UNIVERSITIES OF THE THIRD AGE - Žemaitaityte, Irena; Balčiūnaite, Agne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article reviews the experience of people arranging studies involving information and communication technologies into the University of the Third Age studies organization. Life expectancy is longer and the birth rate is lower in proportion to older age people; due to these facts, the ageing is even more noticeable. This situation requires certain measures, which would be effective in the future. Non-formal education institutions, including University of the Third Age, react to the changes and offer trainings which help older people to maintain working-capacity, physical, social and psychological health. In order to provide greater benefits, it is important to pay attention not only to the students of the Third Age but to the needs and changes of society on the whole. It is obvious that in the twenty-first century life is hardly imaginable without information-communication technologies (ICT), which are not only rapidly growing and modifying but are also integrating and changing each and every one aspects of people`s lives, regardless of their age. Therefore, it is extremely important that elder persons have at least minimal of computer literacy and ICT skills in order to conform to modern society standards.